Integrated Assessment of Productive, Environmental, and Social Performances of Adopting Low-Protein Diets Technology for Laying Hens - Dongsheng Li; Xiaoying Zhang; Zhiyang Zhao; Siqi Wang; Jing Wang; Hongliang Wang (Animals)
China, the world’s largest egg producer, faces challenges of protein feed shortages and nitrogen pollution from manure. Low-protein diets (LPDs) offer potential solutions, but their adoption by small-scale farmers is uncertain. This study used surveys, meta-analysis, life-cycle assessment, and life-cost analysis to address these gaps. A field survey in Quzhou County (a typical representative of small- and medium-scale farmers in China’s egg farming industry) found that 84% of egg farmers were unfamiliar with LPDs and believed higher protein levels were better. On average, pre-laying and late-laying diets exceeded national LPD recommendations by 0.3% and 0.5% crude protein (CP), respectively. The main barriers to LPD adoption were perceived low quality, lack of veterinary recommendations, and limited technical support. A meta-analysis of 30 studies (published before July 2024) showed that reducing CP by less than 1% did not compromise productivity. Local LPD demonstrations and training improved farmer confidence. Results indicated a 10% reduction in the nitrogen footprint and a 115% increase in earnings for LPD-demonstration farmers. The study suggests a coupled pathway integrating research and technology diffusion, highlighting the need for collaboration among scientists, feed companies, and technical experts to overcome misconceptions and promote LPD adoption. This integrated framework offers valuable insights for sustainable agricultural development in China and other resource-limited countries.